Halal Critical Point Analysis of Bajakah Wood (Spatholobus littoralis Hassk.) Nano Particle as Anticancer Agent - Lelly Yuniarti; Yuktiana Kharisma; Titik Respati; Maya Tejasari (Universitas Islam Bandung, 2021)
Bajakah wood contains phenolic compounds, flavonoids, tannins, and saponins with anticancer activity. The discovery and development of new drugs require several stages. In the process, there are many possibilities of adding other substances to form new active substances or as solvents that allow drug preparations to be doubtful of halalness. Hence, it is necessary to analyze the critical point of halal ingredients. The purpose of this study was to determine the characteristics of the nanoparticles of bajakah wood (Spatholobus littoralis Hassk.) and to test the anticancer activity in several cancer cell cultures, as well as to analyze the critical point of halalness of the material. This research method is a composition test using chromatography and anticancer activity test using MTT. Analysis of the critical point of halal materials using hazard analysis critical control point (HACCP). The research was carried out at the Indonesian Engineering Nanotechnology Laboratory South Tangerang and the UGM Integrated Laboratory Sleman in July–December 2020. The results showed that bajakah wood nanoparticles contained pure water as a solvent, viscosity 0.08878 cP, scattering intensity 1.1059 cps, diameter 176.1+/−43.7 (nm). Cytotoxic test results showed IC50 against cell culture MCF7 1,063.28 (±114.98) g/mL, HepG2 53.34 (±0.35) g/mL, T47D 150.63 (±8.44) g/mL, WiDR 114.38 (±7.82) μg/mL, HTB 97.50 (±3.49) μg/mL, HeLa 182.95 (±36.22) μg/mL, and Vero 710.10 (±106.46) μg/mL. This study concludes that bajakah wood nanoparticles are not critical in terms of halal ingredients. At the same time, their anticancer activity is weak against breast cancer and uterine cervical cancer, medium categories against liver cancer and lung cancer, and is not toxic to normal cells. ANALISIS TITIK KRITIS KEHALALAN NANOPARTIKEL KAYU BAJAKAH (SPATHOLOBUS LITTORALIS HASSK.) SEBAGAI AGEN ANTIKANKERKayu bajakah mengandung senyawa fenolik, flavonoid, tanin, dan saponin yang memiliki aktivitas antikanker. Penemuan dan pengembangan obat baru memerlukan beberapa tahapan. Dalam prosesnya terdapat banyak kemungkinan penambahan zat lain untuk membentuk zat aktif baru atau sebagai pelarut yang memungkinkan sediaan obat diragukan kehalalannya. Oleh sebab itu, perlu dilakukan analisis titik kritis kehalalan bahan. Tujuan penelitian ini mengetahui karakteristik sediaan nanopartikel kayu bajakah (Spatholobus littoralis Hassk.) dan menguji aktivitas antikanker pada beberapa kultur sel kanker, serta menganalisis titik kritis kehalalan bahan. Metode penelitian ini adalah uji komposisi menggunakan kromatografi dan uji aktivitas antikanker menggunakan MTT. Analisis titik kritis kehalalan bahan menggunakan hazard analysis critical control point (HACCP). Penelitian dilakukan di Laboratorium Nanovasi Rekayasa Indonesia Tangerang Selatan dan Laboratorium Terpadu UGM Sleman pada Juli–Desember 2020. Hasil penelitian menunjukkan sediaan nanopartikel kayu bajakah mengandung pelarut air murni, viskositas 0,08878 cP, scattering intensity 1,1059 cps, berdiameter 176,1+/−43,7 (nm). Hasil uji sitotoksik menunjukkan IC50 terhadap kultur sel MCF7 1.063,28 (±114,98) μg/mL, HepG2 53,34 (±0,35) μg/mL, T47D 150,63 (±8,44) μg/mL, WiDR 114,38 (±7,82) μg/mL, HTB 97,50 (±3,49) μg/mL, HeLa 182,95 (±36,22) μg/mL, dan Vero 710,10 (±106,46) μg/mL. Kesimpulan penelitian ini bahwa nanopartikel kayu bajakah bersifat tidak kritis dalam kehalalan bahan. Selain itu, aktivitas antikankernya lemah terhadap kanker payudara dan kanker serviks uteri, sedang terhadap kanker hati dan kanker paru, serta tidak toksik pada sel normal.